2012
DOI: 10.1016/j.euromechsol.2012.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic analysis of an adhesive joint with mismatch strain

Abstract: This paper proposes the study of the equilibrium problem, where two elastic bodies are bonded to a thin elastic film under mismatch strain conditions resulting in a state of residual stress. The asymptotic behavior of the film/adherent system is modeled as the film thickness tends to zero, using a method based on asymptotic expansions and energy minimization procedures. This method yields a family of non-local imperfect interface laws, which define a jump in the displacement and the traction vector fields. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In the works of Lebon and Rizzoni [10,11,22,23], a two-level model is introduced in such a manner that the interphase is replaced by a perfect interface at the first level, and by an imperfect interface at the second level, the latter being considered a correction of the leading solution. In [10], they consider an adhesive joint from the point of view of displacement, while [11] extends the work to the anisotropic case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the works of Lebon and Rizzoni [10,11,22,23], a two-level model is introduced in such a manner that the interphase is replaced by a perfect interface at the first level, and by an imperfect interface at the second level, the latter being considered a correction of the leading solution. In [10], they consider an adhesive joint from the point of view of displacement, while [11] extends the work to the anisotropic case.…”
Section: Introductionmentioning
confidence: 99%
“…In [10], they consider an adhesive joint from the point of view of displacement, while [11] extends the work to the anisotropic case. The method is then applied to a thin interphase with a mismatch strain in [22], while [23] deals with a curved thin elastic interphase.…”
Section: Introductionmentioning
confidence: 99%
“…However, defects induced during the manufacturing process or accumulated due to environmental and operational loads lead to the reduction in the mechanical performance and material strength and are recognized as a general problem in this type of composites, [1]. Most typically, such defects can be found at the interfaces between the layers creating an imperfect contact condition, [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach consists in considering that the thickness and the elasticity coefficients of the bond are small parameters compared to those of the other components of the composite. Then, using matched asymptotic expansions, it can be shown that in that case, the behavior of the interphase can be accurately approximated by an interface with an appropriate contact law, where the jump in the displacements is proportional to the stress, which is supposed to be continuous (see, for example, [8][9][10][11]). …”
Section: Introductionmentioning
confidence: 99%